The Urban Child Institute CANDLE Study Methodological Overview and Baseline Sample Description - Sontag-Padilla, Lisa M. (RAND Corporation, 2015)
This report describes the study design and summary data from the first year of data collection for the Urban Child Institute Conditions Affecting Neurocognitive Development and Learning in Early Childhood Study: participant demographics, prenatal and birth measures; child and family health and nutrition; mothers' mental and behavioral health; and cognitive performance, psychosocial measures, and biological samples for mothers and children.